Tindak Tutur Direktif dalam Pidato Perdana Presiden Prabowo Subianto di Kanal Youtube - Gusti, Nila; Ramadhan, Syahrul; Tressyalina, Tressyalina; Afnita, Afnita; Simanjuntak, Nensy Megawati (Universitas Suryakancana, 2025)
This article aims to describe the types of directive speech acts delivered by President Prabowo Subianto in his first speech via the Youtube channel. This study uses a descriptive qualitative method. The data analysis technique uses the Miles and Huberman data model technique, namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this study found the types of directive speech acts, First, request speech acts with a total of 12 utterances with a percentage of 40%. Second, question speech acts with a total of 4 utterances with a percentage of 13.33%. Third, requirement speech acts with a total of 2 utterances with a percentage of 6.66%. Fourth, prohibition speech acts with a total of 4 utterances with a percentage of 13.33%. Fifth, permission speech acts with a total of 0 utterances with a percentage of 0%. Sixth, advice speech acts with a total of 8 utterances with a percentage of 26.66%. Keywords: directive speech acts, speech, youtube ABSTRAK Artikel ini akan mendeskripsikan jenis tindak tutur direktif yang disampaikan oleh Presiden Prabowo Subianto dalam pidato perdananya melalui kanal Youtube. Penelitian dilakukan menggunakan metode kualitatif bersifat deskriptif. Teknik analisis data menggunakan teknik data model Miles dan Huberman yakni, pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan ditemukan jenis tindak tutur direktif, Pertama, tindak tutur permintaan dengan jumlah tuturan 12 tuturan dengan persentase 40%. Kedua, tindak tutur pertanyaan dengan jumlah 4 tuturan dengan persentase 13,33%. Ketiga, tindak tutur persyaratan dengan jumlah 2 tuturan dengan persentase 6,66%. Keempat, tindak tutur larangan dengan jumlah 4 tuturan dengan persentase 13,33%. Kelima, tindak tutur pengizinan dengan jumlah 0 tuturan dengan persentase 0%. Keenam, tindak tutur nasihat dengan jumlah 8 tuturan dengan persentase 26,66%. Kata kunci: tindak tutur direktif, pidato, youtube